Myosin heavy chain isoform composition in the deltoid and vastus lateralis muscles of elite handball players - Mandroukas, A.; Metaxas, T. I.; Papadopoulou, Z.; Heller, J.; Margaritelis, N. V.; Christoulas, K.; Ekblom, B.; Vrabas, I. S. (Journal of Sports Sciences, 2020)
The purpose of the present study was to compare the myosin heavy chain (MHC) isoform composition of the deltoid and vastus lateralis muscles of the dominant and non-dominant limbs in handball players. Eleven male Greek elite handball players (age 22.6 ± 1.9 yrs, training experience 10.6 ± 2.1 yrs, height 184.1 ± 4.1 cm, and weight 81.0 ± 12.5 kg) participated in the study. Four muscle biopsies were obtained from the dominant and non-dominant deltoid and vastus lateralis muscles during the in-season period. The MHC composition was determined using SDS-PAGE. No significant difference was found between the dominant and non-dominant muscles; Deltoid muscle: MHC I [(95%CI = -1.22, 0.33), P = 0.228], MHC IIa [(95%CI = -0.32, 1.59), P = 0.168] and MHC IIx [(95%CI = -1.49, 1.10), P = 0.749]; Vastus lateralis muscle: MHC I [(95%CI = -0.38, 0.63), P = 0.586], MHC IIa [(95%CI = -0.50, 0.65), P = 0.783] and MHC IIx [(95%CI = -1.08, 0.42), P = 0.355]. The findings of the present study indicate that the greater use of the dominant limbs for throwing actions and body movements in handball do not lead to altered MHC isoform composition compared to the non-dominant limbs.